The Relationship Between Serum Neuron-Specific Enolase Levels and Severity of Bleeding and Functional Outcomes in Patients With Nontraumatic Subarachnoid Hemorrhage. Issue 4 (24th November 2015) - Tawk, Rabih G.; Grewal, Sanjeet S.; Heckman, Michael G.; Rawal, Bhupendra; Miller, David A.; Edmonston, Drucilla; Ferguson, Jennifer L.; Navarro, Ramon; Ng, Lauren; Brown, Benjamin L.; Meschia, James F.; Freeman, William D.
Abstract: BACKGROUND: The value of neuron-specific enolase (NSE) in predicting clinical outcomes has been investigated in a variety of neurological disorders. OBJECTIVE: To investigate the associations of serum NSE with severity of bleeding and functional outcomes in patients with subarachnoid hemorrhage (SAH). METHODS: We retrospectively reviewed the records of patients with SAH from June 2008 to June 2012. The severity of SAH bleeding at admission was measured radiographically with the Fisher scale and clinically with the Glasgow Coma Scale, Hunt and Hess grade, and World Federation of Neurologic Surgeons scale. Outcomes were assessed with the modified Rankin Scale at discharge. RESULTS: We identified 309 patients with nontraumatic SAH, and 71 had NSE testing. Median age was 54 years (range, 23-87 years), and 44% were male. In multivariable analysis, increased NSE was associated with a poorer Hunt and Hess grade ( P = .003), World Federation of Neurologic Surgeons scale score ( P < .001), and Glasgow Coma Scale score ( P = .003) and worse outcomes (modified Rankin Scale at discharge; P = .001). There was no significant association between NSE level and Fisher grade ( P = .81) in multivariable analysis. CONCLUSION: We found a significant association between higher NSE levels and poorer clinical presentations and worse outcomes. Although it is still early for any relevant clinical conclusions, our results suggest that NSE holds promise as a tool for screening patients at increased risk of poor outcomes after SAH.